(untitled) (Iranian Journal of Kidney Diseases, 2012)
Hemophagocytic lymphohistiocytosis (HLH) is still an important elusive and misdiagnosed condition despite of improved knowledge. Nephrotic syndrome associated with HLH is not a common feature and has been rarely reported in hemophagocytic syndrome. We report a 27-year-old man with HLH who progressed to multi-organ failure as well as nephrotic-range proteinuria, generalized edema, and hypoalbuminemia.